2020
DOI: 10.1002/cmdc.202000655
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand‐Directed Nitrophenol Carbonate for Transient in situ Bioconjugation and Drug Delivery

Abstract: Here we report the first use of ligand‐directed proximity accelerated bioconjugation chemistry in the tandem delivery and release of a therapeutic payload. To do this, we designed a nitrophenol carbonate for ligand‐directed in situ bioconjugation of a prodrug payload to a protein. The transient nature of our conjugation chemistry renders the protein a depot for time‐dependent release of active drug following hydrolysis and self‐immolation. In our model system, using an immunostimulant prodrug, biotin ligand, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Respect to what happened in the crystal structure, TEP assumes in the binding pocket a different position, being its xanthene moiety oriented toward the outer face of the protein and making a critical H-bond with Thr38 and a π-π stacking with Trp97 (Figure 3A). Similarly, the aromatic part of GUA is stabilized by the interaction with Thr77 and Trp97 in the opposite conformation compared to the one found in the crystal structure 23 (Figure 3B). We believe that this difference is due to the dynamics of the loop, limited to only two conformations by the crystalline packing and which instead allows in silico to reach the correct positioning of the TEP on the minimum energy.…”
Section: Free-energy Of Tep Recognition By Avidinmentioning
confidence: 67%
See 2 more Smart Citations
“…Respect to what happened in the crystal structure, TEP assumes in the binding pocket a different position, being its xanthene moiety oriented toward the outer face of the protein and making a critical H-bond with Thr38 and a π-π stacking with Trp97 (Figure 3A). Similarly, the aromatic part of GUA is stabilized by the interaction with Thr77 and Trp97 in the opposite conformation compared to the one found in the crystal structure 23 (Figure 3B). We believe that this difference is due to the dynamics of the loop, limited to only two conformations by the crystalline packing and which instead allows in silico to reach the correct positioning of the TEP on the minimum energy.…”
Section: Free-energy Of Tep Recognition By Avidinmentioning
confidence: 67%
“…ITC measurements on the avidin-TEP complex (Figure 2) showed that the binding constant K d is 440 μM, in the same μM order to those obtained by fluorescent titration for 8-oxodeoxyguanosine and deoxyguanosine. 23 Compared to its natural ligand this affinity is several orders of magnitude weaker. The thermodynamics of the binding event is characterized by a free-energy (ΔG) of À4.813 kcal/Mol, enthalpy (ΔH) of À5.750 kcal/Mol and entropy (ΔS) of À3.142 kcal/ Mol.…”
Section: Avidin Has Low-affinity For Tepmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (400 MHz, CDCl 3 , 25°C): δ = 7.72 (s, 1H, 3''), 7.30 (m, 2H, 3'), 7.20 (m, 2H, 2'), 7.15 (m, 1H, 4'), 7.14 (s, 1H, 6''), 5.63 (dd, J GEM = 14.9, J 3a-6'' = 0.6, 3a), 5.57 (dd, J GEM = 14.9, J 3b-6'' = 0.6, 3b), 4.23 (m, 2H, À OÀ CH 2 -CH 3 ), 3.97 (s, 3H, 5''À OÀ CH 3 ), 3.97 (s, 3H, 4''À OÀ CH 3 ), 1.76 (s, 3H, 1-CH 3 ), and 1.75 (s, 3H, 1-CH 3 ), 1.32 ppm (td, J CH 3 -CH 2 = 7.1, J CH 3 -P = 1.2, À OÀ CH 2 -CH 3 ). 13 (10). Phenyl dichlorophosphate 17 (60 μL, 0.40 mmol, 1.00 equiv.)…”
Section: 5-dimethoxy-2-nitrobenzyl (2s)-2-((ethoxy(phenoxy)phosphoryl)oxy)-mentioning
confidence: 99%
“…Triggered cargo release can be used in drug delivery [2] (prodrugs, [3] antibody-drug conjugates, [4] and chemosensors [5] ), smart materials [6] (stimuli-responsive SI dendrimers [7] and polymers [8] ), or in vivo cell labelling, [9] thus highlighting the wide range of applications of SI linkers. In turn, different structural motifs, including carbamate [3,6,10] or phosphate, [11] can be used to attach chemically variable cargos to the SI linker.…”
Section: Introductionmentioning
confidence: 99%